FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HEMOROID PADA PASIEN DI POLI BEDAH RSUD RAJA AHMAD TABIB TAHUN 2019-2022 - Rifki, Muhammad; Rusdani, Rusdani; Eryaningrum, Nadia (Universitas Batam, 2023)
Background: Hemorrhoids, also known as piles, are a common medical condition worldwide. Hemorrhoids occur when blood vessels in the anal or rectal area swell and become inflamed. Factors contributing to the occurrence of hemorrhoids include age, occupation, obesity, gender, constipation, and prolonged sitting during bowel movements. This research aims to provide valuable information for the Indonesian community, doctors, and researchers regarding the risk factors associated with hemorrhoid occurrence. Methods: The research design used in this study is an Observational Case Control with a Retrospective approach. The population in this study consisted of patients who visited the surgical department of RSUD Raja Ahmad Tabib from 2019 to 2022, totaling 6,549 patients. Sample selection was done using Simple Random Sampling, with a total sample size of 82 individuals. The research results were analyzed using the Chi-Square test. Results: In this study, the Chi-Square test analysis revealed factors related to the occurrence of hemorrhoids: Based on Age (p=0.672), Based on Gender (p=0.004), Based on Obesity (p=0.049), and Based on Occupation (p=0.000). Conclusion: Based on the research findings, it can be concluded that there is a significant association between Gender, Obesity, and Occupation with the occurrence of hemorrhoids among patients in the surgical outpatient department of Raja Ahmad Tabib Regional General Hospital from 2019 to 2022.